Multimedia With Digital Presentation in Foreign Language: Its Implication to Useful Learning: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Education is continually changing, and new technological advancement can affect manyventures, particularly in advancing teaching methodologies. The Philippines is considered ahome to many immigrants, which is reflected in its wide variety of Foreign Languages. Withthe rapid growth and availability of technology, language is incorporating different additionalaids to learn the language with the help of Multimedia to make their task easier and moredynamic. According to Webster's Dictionary, Multimedia is defined as training or educationalmaterials directed at both the senses of hearing and the sense of sight, films, recordings,photographs, and GIFs that are used in classroom instruction. Multimedia is one of the mostcommon needs in our education program, which is used in the classroom to encouragelearning and make a process to make it easier and more interesting. Multimedia is the bestdevice for making an effective way of learning process and the best tool for the disseminationof knowledge in one classroom. The goal of Multimedia is to enhance strategies and to helpstudents understand the lesson easily. Multimedia no doubt reflects that technical deviceshave a greater impact and dynamic, informative systems.The researchers included the purpose, role, and benefits of 21st-century learning beforeintroducing multimedia when using multimedia in a foreign language, which is the main focusof the study. The researchers find it appropriate to utilize the descriptive method in line withthe concerned research on digital presentation with multimedia in foreign languages and itsImplications for useful learning.The findings of the data show that video presentation has the highest mean value in thedescriptive scale, which is the most useful compared to the other types of multimedia inlearning a foreign language. The researchers discovered that respondents find multimedia tobe extremely useful in learning a foreign language, particularly in terms of expanding anddeveloping their vocabulary.
Keywords: Psychology